Advances in in vitro genetic code reprogramming in 2014–2017. Issue 1 (31st May 2018) - Katoh, Takayuki; Passioura, Toby; Suga, Hiroaki
Abstract: To date, various genetic code manipulation methods have been developed to introduce non-proteinogenic amino acids into peptides by translation. However, the number of amino acids that can be used simultaneously remains limited even using these methods. Additionally, the scope of amino acid substrates that are compatible with ribosomal translation systems is also limited. For example, difficult substrates such as d -amino acids and β-amino acids are much less efficiently incorporated into peptides than l -α-amino acids. Here, we focus on three recently developed methodologies that address these issues: (i) artificial division of codon boxes to increase the number of available amino acids, (ii) orthogonal ribosomal translation systems to 'duplicate' the codon table and (iii) development of novel artificial tRNAs that enhance incorporation of difficult amino acid substrates.